PENGARUH KADAR HIGH DENSITY LIPOROTEIN (HDL) DENGAN PENURUNAN HOT FLASHES PADA MENOPAUSE DENGAN SENAM LANSIA - Bela Purnama Dewi; Diana H. Soebyakto (LPPM STIKes Mitra Adiguna, 2024)
Estrogen is a hormone that plays an important role in preventing the oxidation process of bad cholesterol (LDL). This hormone also plays a role in balancing bad cholesterol (LDL) and good cholesterol (HDL) levels in the body. Based on data taken by WHO, women experiencing menopause worldwide have reached 476 million and it is estimated that by 2030 this will increase to 1.2 billion women. Hot flashes are experienced by approximately 70-80% of menopausal women. A peri or post-menopausal woman can experience complaints in the form of hot flashes or sweating which are categorized as vasomotor symptoms. This research aims to determine the effect of High Density Lipoprotein (HDL) levels on reducing hot flashes in menopause with elderly exercise. This research is quantitative research. The design used in this research was Pre Experimental using a one group pre post test design. The results of this study show that the results of the paired T test for the HDL value at post-intervention were 0.002 < 0.05. It can be concluded that there is an influence on the HDL value and reducing hot flashes in menopause with exercise for the elderly. The advice given is that it is hoped that people can implement it in their daily lives by doing routine elderly exercise to maintain physical health and control cholesterol in menopausal women who experience hot flashes.